Dominica : 2010 Article IV Consultation; Staff Report; Staff Supplement and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The Dominican economy has been more resilient to the global crisis than other ECCU countries. Executive Directors welcomed the Growth and Social Protection Strategy, which is aimed at fostering growth and reducing poverty while lowering public debt. Directors also welcomed the authorities' regional approach to address the collapse of the Trinidad and Tobago-based CL Financial Group. They encouraged the authorities to reduce the debt-to-GDP ratio to respond to external shocks. Directors commended the prudent fiscal policy stance and stressed the importance of strengthening the financial sector.